2018
DOI: 10.3389/fimmu.2018.01122
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of the Immune System and Vitamin D Levels in Old Individuals

Abstract: AimThe increased number of individuals older than 80 years, centenarians, and supercentenarians is not a synonym for healthy aging, since severe infections, hospitalization, and disability are frequently observed. In this context, a possible strategy is to preserve the main characteristics/functions of the immune system with the aim to cause less damage to the organism during the aging process. Vitamin D acts on bone marrow, brain, breast, malignant cells, and immune system and has been recommended as a supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 83 publications
1
35
0
1
Order By: Relevance
“…Due to a lack of sun exposure and decreased production of vitamin D, about half of all older people have a deficiency in this vitamin [53], which reduces the efficacy of both adaptive and innate immune responses and increases the risk of infection [54]. Vitamin D levels in older people are correlated with preserved features of immunity such as the CD4 + /CD8 + ratio and lower levels of pro-inflammatory cytokines after stimulus [54,55].…”
Section: Agingmentioning
confidence: 99%
“…Due to a lack of sun exposure and decreased production of vitamin D, about half of all older people have a deficiency in this vitamin [53], which reduces the efficacy of both adaptive and innate immune responses and increases the risk of infection [54]. Vitamin D levels in older people are correlated with preserved features of immunity such as the CD4 + /CD8 + ratio and lower levels of pro-inflammatory cytokines after stimulus [54,55].…”
Section: Agingmentioning
confidence: 99%
“…Currently, there is convincing evidence that the numbers of immunosuppressive MDSCs increases with aging in the blood of both humans [158,159] and mice [160]. Several studies have also revealed an age-related increase in the accumulation of MDSCs into mouse bone marrow, spleen, and lymph nodes [160,161].…”
Section: Activation Of Immunosuppressive Network With Aging and Alzhementioning
confidence: 99%
“…There is convincing evidence that the aging process increases the frequencies of circulating MDSCs, in both humans [ 108 , 109 ] and mice [ 110 ]. Verschoor et al [ 108 ] revealed that the levels of the CD11b + CD15 + -positive, granulocytic MDSCs were increased in the blood of community-dwelling seniors (61–76 years) and especially in frail elderly people (67–99 years).…”
Section: Introductionmentioning
confidence: 99%
“…Verschoor et al [ 108 ] revealed that the levels of the CD11b + CD15 + -positive, granulocytic MDSCs were increased in the blood of community-dwelling seniors (61–76 years) and especially in frail elderly people (67–99 years). Recently, Alves et al [ 109 ] demonstrated that the percentage of MDSCs was significantly higher in the blood of old people (80–100 years) than in their younger counterparts (20–30 years). Especially, the percentage of granulocytic MDSCs was robustly upregulated, while that of monocytic MDSCs was unaffected.…”
Section: Introductionmentioning
confidence: 99%